Functional characterization of a novel TP53RK mutation identified in a family with Galloway–Mowat syndrome. Issue 12 (27th September 2022) - Treimer, Ernestine; Kalayci, Tugba; Schumann, Sven; Suer, Ilknur; Greco, Sara; Schanze, Denny; Schmeisser, Michael J.; Kühl, Susanne J.; Zenker, Martin
Abstract: Galloway–Mowat syndrome (GAMOS) is a very rare condition characterized by early‐onset nephrotic syndrome and microcephaly with variable neurologic features. While considerable genetic heterogeneity of GAMOS has been identified, the majority of cases are caused by pathogenic variants in genes encoding the four components of the Kinase, endopeptidase, and other proteins of small size (KEOPS) complex, one of which is TP53RK . Here we describe a 3‐year‐old male with progressive microcephaly, neurodevelopmental deficits, and glomerular proteinuria. He was found to carry a novel homozygous TP53RK missense variant, c.163C>G (p.Arg55Gly), which was considered as potentially disease‐causing. We generated a morpholino tp53rk knockdown model in Xenopus laevis showing that the depletion of endogenous Tp53rk caused abnormal eye and head development. This phenotype could be rescued by the expression of human wildtype TP53RK but not by the c.163C>G mutant nor by another previously described GAMOS‐associated mutant c.125G>A (p.Gly42Asp). These findings support the pathogenic role of the novel TP53RK variant.